Metroglyph analysis in Trichosanthes dioica (Roxb.) (Journal of Bio-Science, 2018)
Morphological variation in eighteen lines of pointed gourd (Trichosanthes dioica Roxb.) was determined by Metroglyph method showing their genetic relationship. Assessment of variability of pointed gourd may help for successful utilization of its different attributes in developing suitable genotypes for yield and stability. A total of twelve quantitative characters were used for analyzing genetic variation. Arbitarily the clusters were found in the diagram but not in consolidated form. Cluster I was represented only by two lines. Almost similarly cluster II was found to be comprised of only three lines. On the contrary, cluster III contains thirteen lines of pointed gourd, although they were found to be located scattered showing their great morphological variations.J. bio-sci. 25: 67-72, 2017